Quantifying molecular oxygen isotope variations during a Heinrich stadial - C. Reutenauer; A. Landais; T. Blunier; C. Bréant; M. Kageyama; M.-N. Woillez; C. Risi; V. Mariotti; P. Braconnot (Climate of the Past, 2015)
δ18O of atmospheric oxygen (δ18Oatm) undergoes millennial-scale variations during the last glacial period, and systematically increases during Heinrich stadials (HSs). Changes in δ18Oatm combine variations in biospheric and water cycle processes. The identification of the main driver of the millennial variability in δ18Oatm is thus not straightforward. Here, we quantify the response of δ18Oatm to such millennial events using a freshwater hosing simulation performed under glacial boundary conditions. Our global approach takes into account the latest estimates of isotope fractionation factor for respiratory and photosynthetic processes and make use of atmospheric water isotope and vegetation changes. Our modeling approach allows to reproduce the main observed features of a HS in terms of climatic conditions, vegetation distribution and δ18O of precipitation. We use it to decipher the relative importance of the different processes behind the observed changes in δ18Oatm. The results highlight the dominant role of hydrology on δ18Oatm and confirm that δ18Oatm can be seen as a global integrator of hydrological changes over vegetated areas.